Inductive method for measuring humidity of heterogeneous dispersed dielectrics - Kukharchuk, V. V.; Bohachuk, V.V.; Hraniak, V. F. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Method of noncontact, nondestructive control for measuring humidity of the material, which can be used for the certification of end products at processiing enterprises of agricultural branch, specialized on the production of foot products, which are heterogeneous dispersible dielectrics, is offered, a general mathematical model for transducers based on this method is developed in the paper.